Consumption Poverty in the Republic of Kosovo in 2009 : Western Balkans Programmatic Poverty Assessment - World Bank; Statistical Office of Kosovo (World Bank and Statistical Office of Kosovo, Prishtina, 2013)
Since the end of armed conflict in 1999, progress on improving living standards in the Republic of Kosovo has been slow and uneven, despite solid macroeconomic performance. Kosovo weathered the economic crisis in 2008-09 better than most countries in South Eastern Europe (SEE). Even so, this growth was modest, constrained by a worsening investment climate, a drop in foreign direct investment, poor governance and rule of law, and growing rent seeking behavior (World Bank 2010). Remittances from the sizeable out-migrant population also declined following the onset of the crisis. Thus Kosovo remains the poorest country in South Eastern Europe. The approach reflects a broader shift in the World Bank's analytical work on poverty in the Western Balkans, placing greater emphasis on shorter and more frequent poverty updates as new data become available. This poverty update is based on the household budget survey (HBS) conducted in 2009. Even though Kosovo appears to have suffered less from the economic crisis than most countries in Europe, it remains one of the poorest countries in Europe. Kosovo's population is exceptionally young, and children and youths are disproportionately poor. Education and employment are intimately related to poverty status. In the aggregate, Kosovo's extremely high unemployment rate is another important driver of its high poverty levels. More rapid employment growth is needed not only to help today's adults, but also to accommodate the rapidly growing youth population that is entering the labor force, and will continue to do so for many years to come.